Mortality and cancer incidence in Swedish battery workers exposed to cadmium and nickel. Issue 11 (November 1998) - Järup, L; Bellander, T; Hogstedt, C; Spång, G
Abstract : OBJECTIVE: To follow up cancer incidence and mortality in a group of Swedish battery workers exposed to nickel hydroxide and cadmium oxide. METHODS: 869 workers, employed at least one year between the years 1940 and 1980 were followed up until 1992. Vital status and causes of death were obtained from the Swedish cause of death registry. Cancer morbidity was retrieved from the Swedish cancer registry. Regional reference rates were used to compute the expected numbers of deaths and cancers. RESULTS: Up to 31 December, 1992, a total of 315 deaths (292 in men and 23 in women) had occurred in the cohort. For men, the overall standardised mortality ratio (SMR) was 106 (95% confidence interval (95% CI) 93.7 to 118) and for women 83.8 (95% CI 53.1 to 126). The SMRs for total cancer mortality were 125 (95% CI 98.2 to 157) for men and 69.5 (95% CI 25.5 to 151) for women. The SMR for lung cancer in men was 176 (95% CI 101 to 287). No lung cancers were found among female workers. Up to 31 December, 1991, a total of 118 cancers had occurred in the cohort. A significantly increased standardised incidence ratio (SIR) was found for cancer of the nose and nasal sinuses in men, three cases v 0.36 expected, yielding an SIR of 832 (95% CI 172 to 2430). Applying a 10 year latency period in cohort members exposed to > or = 1000 micrograms cadmium/m3, the SIR was 1107 (95% CI 134 to 4000). Similarly, for cohort members exposed to 2000 micrograms nickel/m3, the SIR was 1080 (95% CI 131 to 3900). CONCLUSION: There was an increased overall risk for lung cancer, but no exposure-response relation between cumulative exposure to cadmium or nickel and risk of lung cancer. There was a highly significant increased risk of cancer of the nose and nasal sinuses, which may be caused by exposure to nickel or cadmium or a combination of both exposures.